Intellectual Capital of Malaysian Banks - Alim, Dee; Rossazana, Binti Ab-Rahim; Noor Shazreen, Binti Mortadza (Human Resource Management Academic Research Society, 2019)
The importance of intellectual capital has induced drastic movement in conducted of businesses by switching from traditional labour to knowledge labour whereby to compete with the incumbents and the newcomers. On this note, services sector especially banking industry plays a vital role in the development of economies that affected overall in gross domestic product compared to the other production sectors thus intellectual capital is important to the growth of banking sector in a nation. Therefore, the general objective of this study is to investigate the intellectual capital of Malaysian banks over the study period of 2007 to 2016 by employing Model of Value Added Intellectual Coefficient (VAIC). In view of the above scenarios, the specific objectives of this study is to investigate the sources of intellectual capital namely human capital efficiency (HCE), structural capital efficiency (SCE) and capital employed efficiency (CEE) of the Malaysian banking institution. The results of this study show that human capital efficiency is the most influential components in the intellectual capital among Malaysian banks. Thus, the findings of this study recommend on the bank’s management and policy makers to increase on the efforts to encourage the utilizing in human capital which is treated as an effective alternatives in creating bank's value as well as consider the human capital as a single resources of the intellectual capital in improving on the efficiency performance of the banks.